ABO blood grouping in Egyptian children with rotavirus gastroenteritis - Elnady, Hala Gouda; Samie, Ola M. Abdel; Saleh, Maysa Tawhid; Sherif, Lobna S.; Abdalmoneam, Naglaa; Kholoussi, Naglaa M.; Kholoussi, Shams M.; EL-Taweel, Ahmed N. (Gastroenterology Review/Przegląd Gastroenterologiczny, 2017)
Introduction : Rotavirus gastroenteritis is an important public health problem all over the world, causing a notable economic burden in both developing and developed countries. Aim: To explore the relationship between blood group typing, rotavirus gastroenteritis, and its severity in Egyptian children. Material and methods: A cross sectional case control study was conducted on 231 cases of acute gastroenteritis attending the outpatient clinic of Al-Zahraa University Hospital. Full history taking, clinical examination, and clinical data collection were done. Blood samples were collected for an ABO grouping. Stool samples were tested for viral gastroenteritis agents. Results : Rota positive cases of GE were significantly more prevalent among cases with blood group A (p < 0.05) and significantly less among cases with blood group B (p < 0.05). The rate of hospitalisation was highly significantly greater among cases with group A (p < 0.005), and significantly lower among cases with group AB and O (p < 0.05). As regards the degree of dehydration, moderate and severe cases were highly significant in groups A and O (p < 0.005). Rota-positive gastroenteritis showed significant positive correlations with indicators of severity such as hospitalisation, degree of dehydration, and duration of fever (p < 0.005). Conclusions : Blood group A is highly associated with paediatric rotavirus gastroenteritis. This could highlight an important risk factor, which could play a significant role for the pathogenesis of rotavirus gastroenteritis and severity as well. Furthermore, more intervention care could be needed for blood group A paediatric patients, if gastroenteritis especially rotavirus affect this group to avoid comorbidities.